Criminologists, duct tape, and Indigenous peoples: quantifying the use of silencing research methods. Issue 1 (2nd January 2016) - Deckert, Antje
Abstract : A recent quantitative evaluation of mainstream criminological research found that there is a dearth of research on "Indigenous peoples in the criminal justice context" conducted in Australia, Canada, New Zealand, and the United States and published in elite criminology journals while these nations continue to incarcerate Indigenous peoples at markedly disproportionate rates. Although the silence prohibits public attention to this social issue, counter-colonial critics have mostly focused on criminologists who deliberately marginalize Indigenous peoples through use of inappropriate research methods. This study is a first attempt to quantify the use of "silencing research methods" in contemporary mainstream criminology. It involves a comprehensive review of research published in elite criminology journals over the past decade (2001–2010). The findings reveal that although mainstream criminologists generally prefer non-silencing research tools, they primarily employ silencing research methods when studying Indigenous peoples. Also, studies that focus on Native American peoples use silencing research tools more often than studies on other disproportionately incarcerated social groups, i.e., African and Hispanic Americans. The study concludes that by using "silencing research methods, " elite mainstream criminology has contributed to the marginalization of Indigenous peoples to varying degrees in all four countries over the past decade.